A session-to-session examination of homework engagement in cognitive therapy for depression: Do patients experience immediate benefits?. (September 2015) - Conklin, Laren R.; Strunk, Daniel R.
Abstract: Homework is a key component of Cognitive Therapy (CT) for depression. Although previous research has found evidence for a positive relationship between homework compliance and treatment outcome, the methods used in previous studies have often not been optimal. In this study, we examine the relation of specific aspects of homework engagement and symptom change over successive session-to-session intervals. In a sample of 53 depressed adults participating in CT, we examined the relation of observer-rated homework engagement and session-to-session symptom change across the first five sessions. Within patient (and not between patient) variability in homework engagement was significantly related to greater session-to-session symptom improvements. These findings were similar when homework engagement was assessed through a measure of general engagement with homework assignments and a measure assessing engagement in specific assignments often used in CT. Secondary analyses suggested that observer ratings of the effort patients made on homework and the completion of cognitive homework were the numerically strongest predictors of depressive symptom improvements. Patient engagement with homework assignments appears to be an important predictor of early session-to-session symptom improvements. Future research is needed to identify what therapist behaviors promote homework engagement. Highlights: Examines the relationship of homework and session-to-session symptom improvements. CT-specific homework was related to improvement in depression symptoms. General homework (time, frequency, effort) also related to depression improvements.